Cloning and expression of a novel phytase gene (phyMS) from Mycobacterium smegmatis - Nuge, Tamrin; Hashim, Yumi Zuhanis Has-Yun; Farouk, Abd-El Alziem; Mohd. Salleh, Hamzah (Scientific Research Publishing Inc., 2014)
Phytase, also known as phytate-degrading enzyme, catalyzes the hydrolysis of phytate (inositol hexakisphosphate) with sequential release of phosphate and lower inositol phosphate. We report here a new plasmid construct designated as pMSuia from pBAD-TOPO that harbors a 1.1 kb phytase gene (phyMS) from Mycobacterium smegmatis, and expression as well as characterization of the purified recombinant M. smegmatis phytase. DNA sequencing analysis and multiple alignment exercise indicated that the M. smegmatis phytase is different from both known acid and alkaline phytases. The active ~45 kDa recombinant enzyme was expressed and confirmed by enzyme assay and Western blot analyses. Ni-NTA affinity purified recombinant M. smegmatis phytase exhibited specific activity of 233.51 U/mg, optimal pH of 3 and 7 and optimal temperature of 60˚C. The purified enzyme retains almost 30% of the initial activity after incubation at 90˚C for 60 min. The enzyme showed broad substrate specificity with Km and Vmax of the recombinant enzyme for sodium phytate substrate of 0.105 ± 0.016 mM and 26.93 ± 1.21 mM min−1, respectively.